2020
DOI: 10.1111/risa.13536
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Analysis of Dam Accidents Worldwide: Risk Assessment for Dams of Different Purposes in OECD and Non‐OECD Countries with Focus on Time Trend Analysis

Abstract: This study presents probabilistic analysis of dam accidents worldwide in the period 1911-2016. The accidents are classified by the dam purpose and by the country cluster, where they occurred, distinguishing between the countries of the Organization for Economic Cooperation and Development (OECD) and nonmember countries (non-OECD without China). A Bayesian hierarchical approach is used to model distributions of frequency and severity for accidents. This approach treats accident data as a multilevel system with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, available models were developed by U.S. institutions that used LL rates empirically derived from historical data on flood events that mostly happened in the USA (see Section 2.2). The direct application of these LL rates to Switzerland would provide a potentially questionable approximation, since it has been shown that accident frequency and severity strongly depend on dam characteristics and location (Kalinina et al, 2017).…”
Section: Study Goalsmentioning
confidence: 99%
“…However, available models were developed by U.S. institutions that used LL rates empirically derived from historical data on flood events that mostly happened in the USA (see Section 2.2). The direct application of these LL rates to Switzerland would provide a potentially questionable approximation, since it has been shown that accident frequency and severity strongly depend on dam characteristics and location (Kalinina et al, 2017).…”
Section: Study Goalsmentioning
confidence: 99%